(3GdTQGHs - (3eMeO Hf RcQjG GdnqQGRj, CHh HcQ,J (B311 (3g` s
(3ChdgG (B:s
(3hgh ebGdJGf (B: (3GdebGdI GdChdi ef cJGHg SJI hYTQhf HGHkG , GdebGdI GdKGfjI JSYI YTQ HGHkG , CHhGH GdChdi (B: (3GdHGH (B( (3C (B) (3ai SHH GdcJGH hai LedI efGaY GdTQGH , GdHGH H ai eVGQ GdTQGH s
(3BNQgG (B:s
(3eG GQOfG Cf fHjf gPg GdeaQOGJ GdJi JQcH hjSgd GSJNQGL eGde fPcQg efgG s
(3GfXQg eY GdWH GdbTJGdi Qbe (B"581"s
(3cJHJ SfI (B1424(3es
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B123 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdhWfjI HeOQjO (B(5/5240) s
Keywords: (3GdWHs